Data from: assessing the suitability of a one-time sampling event for close-kin mark-recapture: a caribou case study ... - Merriell, Brandon; Manseau, Micheline; Wilson, Paul (Dryad, 2025)
This dataset contains the R scripts and data files utilized by the associated manuscript of the same name. It includes the R script for performing the close-kin mark-recapture simulation study, as well as the R script for performing the close-kin mark-recapture case study on a small boreal caribou population. Additionally, it includes the capture histories, life-stage assignments, and multilocus genotypes for the caribou case study. It also includes the necessary input files for the COLONY software to infer parentage for the caribou case study, as well as the maternity assignment file output by COLONY. ... : # Data from: assessing the suitability of a one-time sampling event for close-kin mark-recapture: a caribou case study [https://doi.org/10.5061/dryad.jh9w0vtk2](https://doi.org/10.5061/dryad.jh9w0vtk2) This dataset contains the various data files and R scripts utilized in the manuscript entitled 'Assessing the suitability of a one-time sampling event for close-kin mark-recapture: A caribou case study.' ## Description of the data and file structure Capture_History_2006-2015.csv - This file contains the capture record for each sample, as uniquely identified by the PCID (2nd column). Samples with the same Cluster_ID (1st column) represent samples from the same individual caribou -- the only exception to this are Cluster_ID of 0, these represent unique singletons (unique individuals for which there is only a single sample). Columns 2-28 represent capture occasions. Column 29 contains the numeric population assignment code, and column 30 contains the sex of each sample (1=female, 2=male, 0=unknown). ...